Mapping the Literature on Ibn Khaldun's Contribution to Economics - Syahdatul Maulida; Rusydiana, Aam Slamet (Islamic Economics and History, 2023)
This study aims to observe the evolution of research focusing on "Ibn Khaldun's Thought in economics" published in various journals around the world. The method used is a qualitative approach with bibliometric analysis using R software. The data used are secondary data related to the theme "Ibn Khaldun's Thought in economics" obtained from the Scopus database. A total of 52 documents covering the period from 1964 to October 16, 2023 were used in the analysis. The results showed that the trend in the number of documents examining Ibn Khaldun in the context of economics tends to increase, reaching its peak in 2021 with a total of 7 documents. The highest average number of citations per year was recorded in 2018, reaching 1.4 citations. In addition, "Humanomics" is the main journal that publishes the highest number of papers on the theme of Ibn Khaldun in economics. The most prolific author in publishing articles on Ibn Khaldun's themes in economics indexed in Scopus is Astuti. In this analysis, three research clusters can be identified based on the co-occurance network.